Single Atom Substitution for Marking and Motion Tracking of Individual Molecules by Scanning Tunneling Microscopy - Schull, Guillaume; Ness, Hervé; Douillard, Ludovic; Fiorini-Debuisschert, Céline; Charra, Fabrice; Mathevet, Fabrice; Kreher, David; Attias, André-Jean (Journal of physical chemistry. C, 2008)
We report on a simple way to mark and track individual molecules self-assembled on a surface by scanning tunneling microscopy. The tracer mechanism consists in a minimal one-atom chemical substitution. While this substitution leads to significant modifications in the STM signature of the molecules, no substantial changes of the physics of self-assembling are observed when using the modified or unmodified molecular building blocks. This allows us to follow the intrinsic dynamical properties of the self-assembled molecular patterns.